KAJIAN MENGENAI PERCERAIAN MENURUT PEMIKIRAN RAJA ALI HAJI: REFLEKSI SYAIR SULUH PEGAWAI - Sibarani, Citra Dewi; Buduroh, Mamlahatun (Jurnal Ilmu Budaya, 2024)
The manuscript of Syair Suluh Pegawai is a literary work authored by Raja Ali Haji, addressing aspects of marital life, including divorce. This syair serves as a guide for officials involved in marital affairs. In addition to outlining marriage guidelines and regulations, Raja Ali Haji also incorporates verses concerning divorce cases, notably through the narrative "Kawin Cina Buta" found within the text of "Syair Lebai Guntur." This study examines divorce in Raja Ali Haji's perspective employing a textual approach within a historical context centered on the author. The research methodology adopted is qualitative descriptive. Analysis reveals that Raja Ali Haji provides marital guidelines rooted in Islamic law, encompassing issues such as different types of divorce—khulu bertalak, talak bid’i, talak makruh, talik talak, and issues related to the pronunciation of talak. To elucidate these guidelines, Raja Ali Haji employs the story of "Kawin Cina Buta" as an illustrative example for understanding divorce matters.